Diferenciación textural y mineralpogica de los minerales de Terrazas y bajos de la Cuenca del Río Guadalete. - Caballero, M.A.; Sánchez Bellón, A.; Gutiérrez Mas, J.M.; López-aguayo, F.; Moral Cardona, J.P. (Cuadernos de Geología Ibérica, 1997)
Various terrace leveis of the present day course of the Guadalete viva have been studicd with the aim of finding differences between the deposits. Mineralogical ~rnd xnorpboscopic features of the quartz gratis diflerences xx'ere found between the low anó high terrace leveis. Although Ihe mineralogical associations of both clay aud hcavv mineral fractions are simular iii the two leveis: (smectite, illite and kaolinite+cblorite) aud (garnet,zireón, epidote ant! andalusite) respectively. The lower leveis are constituted by sands with 60% of quartz aud 21% of calcite, while ÍD the highest leveis grave) dominates wliich is formed by pebbles of limestone, sandstone, chert aud ophitic materiais, from the Cordillera Hética, being the sandy fraction most quartzitic (80% of quarf.z and 1 2% of caRite). Tbis is interpreted as a consecuence of the presence of different materlais along the river's eonrse aud also because the evolution of tIie hasin from a tuctonicly active pitase fo more stable one. The predominance of angular quartz grains witb mechanic superficial textures (conéhoidal fractures) jo the lower terrace leveis aná subronuded gratis with suJ)erhcial textures of chemical origin (disolution aud deposits of silica> iii the highest leveis, sliow thc biggest evolution grade of fliese aud the beginning of an edafie phase.
Keywords: Surface features; quariz; morphoscopy; terraces; Guadalete ci ver